Attitude Tracking of Rigid Spacecraft with Actuator Saturation and Fault Based on a Compound Control. (28th December 2020) - Cheng, Chunhua; Yang, Hang; Wang, Qian; Li, Lin; Han, Qiang; Ouyang, Huan; Ma, Haiyang; Lv, Xinyi
Abstract : A compound control based on active disturbance rejection control (ADRC) scheme and slide mode control (SMC) is proposed to investigate the attitude tracking problem for a spacecraft with modeling uncertainties, external disturbances, actuator failures, and actuator saturations simultaneously. A positive term including control input is separated from the system, and then, the active disturbance rejection concept and the extended state observer (ESO) are applied to deal with the general uncertain item caused by uncertainties, external disturbances, actuator failures, and actuator saturations. The sliding mode surface is designed to transform the attitude tracking problem into attitude stabilization problem. In order to deal with the actuator saturations, a saturation degree coefficient and its corresponding adaptive law are introduced. Compared to other existing references, the proposed scheme does not need to know the structure or upper bound information of the inertial matrix uncertainties and external disturbances. Finally, the stability of the closed-loop system is analyzed by using input to state stability theory. Simulation results are given to verify the effectiveness of the proposed scheme. More importantly, the proposed technique can also be applied to the attitude stabilization of other aircraft, such as the attitude of unmanned aerial vehicle and helicopter in maritime rescue.